2019
DOI: 10.1177/1352458518820272
|View full text |Cite
|
Sign up to set email alerts
|

Trait Conscientiousness predicts rate of longitudinal SDMT decline in multiple sclerosis

Abstract: Background: Many people with multiple sclerosis (MS) exhibit cognitive decline over several years. Baseline differences may put people at greater risk for such decline. Objective: To characterize rates of longitudinal cognitive decline and investigate baseline clinical predictors. Methods: We report a retrospective analysis of 531 MS patients whose data were gleaned from a multi-study database, aggregated over 16 years. Linear mixed effects modeling was applied to estimate the average rate of decline on Symbol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
(67 reference statements)
2
16
0
1
Order By: Relevance
“…Interestingly, in our study, we did not see a commensurate reduction in performance on the SDMT, the proposed gold standard measure 27,43 that similarly places demands on visual WMem and processing speed 44,45 ; indeed all pwMS identi ed as impaired by the SDMT were also identi ed by the OM n-back. This is in line with previous studies that have similarly found that the SDMT's ability to detect cognitive deterioration within 2-3 years is poor 46,47 , with performance estimated to decrease by only .22 decrease per year 48 . This may represent a combination of practice effects and the sensitivity of the measure to subtle change.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in our study, we did not see a commensurate reduction in performance on the SDMT, the proposed gold standard measure 27,43 that similarly places demands on visual WMem and processing speed 44,45 ; indeed all pwMS identi ed as impaired by the SDMT were also identi ed by the OM n-back. This is in line with previous studies that have similarly found that the SDMT's ability to detect cognitive deterioration within 2-3 years is poor 46,47 , with performance estimated to decrease by only .22 decrease per year 48 . This may represent a combination of practice effects and the sensitivity of the measure to subtle change.…”
Section: Discussionsupporting
confidence: 92%
“…9 Recently, this trait was shown to predict deterioration in cognition and brain volume over 5 years in multiple sclerosis (MS). 10,11 Low Conscientiousness is also associated with occupational stress in MS workers. 12…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, this trait was shown to predict deterioration in cognition and brain volume over 5 years in multiple sclerosis (MS). 10,11 Low Conscientiousness is also associated with occupational stress in MS workers. 12 A limitation of cross-sectional associations between these factors and employed/disabled status is that metrics of change or potentially actionable antecedents to job loss are missed.…”
mentioning
confidence: 99%
“…[3][4][5] Higher Conscientiousness also predicts slower rates of cognitive decline in PwMS. 6 To our knowledge, there is no investigation of the relationship between Conscientiousness and brain atrophy using a longitudinal study design in PwMS. Herein, we report analysis of a large retrospective cohort with multiple magnetic resonance imaging (MRI) evaluations over 15 years.…”
Section: Introductionmentioning
confidence: 99%